PENGARUH MODEL PEMBELAJARAN INDUKTIF DAN SELF-CONFIDENCE TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIK SISWA KELAS V SEKOLAH DASAR - Muhamad Dawam Raihan; Cecep Anwar Hadi Firdos Santosa; Yumiati (Jurnal Pendidikan Dasar, 2021)
The purpose of this study is to determine the differences in the ability to understand mathematical concepts of students who are taught by using inductive approaches and conventional learning and the differences in the ability to understand mathematical concepts of students who have high and low self-confidence. In addition, this study aims to determine the effect of the interaction between learning approaches and self-confidence on the ability to understand mathematical concepts. This research was carried out at SDN Pasauran 1, Cinangka District. The method used in this research is a quasi-experimental design with 2x2 level treatment. The data collection technique was a concept understanding test and a student self-confidence questionnaire. Testing the research hypothesis using two-way analysis of variance. Before testing the hypothesis, the data must meet the assumptions of normality and homogeneity, the test results show that the data is normally distributed and homogeneous. The results of the two-way analysis of variance test show that: there is a significant difference between students who are taught through inductive approach learning and conventional learning, there is a significant difference between students who have high and low self-confidence, there is an interaction effect between the learning approach and self-confidence on the ability to understand mathematical concepts and there are differences in the ability to understand mathematical concepts between students who are taught through inductive and conventional learning approaches, both for students who have high and low self-confidence.